Efficacy of intraoperative subanesthetic dose of ketamine/esketamine in preventing postoperative cognitive dysfunction: a systematic review and meta-analysis - Na Zhou; Chengchuan Chen; Yubei Liu; Zhaolan Yu; Yanhua Chen (SAGE Publishing, 2023)
Background: Postoperative cognitive dysfunction (POCD) is a common complication after anesthesia surgery, especially in older people, that can persist weeks or months after surgery as a short-term impairment of cognitive abilities, or even for a prolonged duration over years, potentially progressing into permanent cognitive dysfunction. However, the pathogenesis of POCD is not fully understood, and therefore an optimal solution for preventing POCD has yet to be established. Some studies have shown that intraoperative ketamine/esketamine reduces the incidence of POCD, but this remains controversial. Objectives: We evaluated the effect of intraoperative subanesthetic doses of ketamine/esketamine versus no intervention in adults undergoing general anesthesia surgery on the incidence of POCD. Data Sources: We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and searched the PubMed, Embase, Ovid, Cochrane, Scopus, and Web of Science databases for the MeSH terms 'ketamine', 'esketamine', and 'Postoperative Cognitive Complications' from database inception to 25 June 2023. Results: We found no statistically significant difference in the incidence of POCD within 7 days for intraoperative subanesthetic dose of ketamine/esketamine compared with the control group [relative risk (RR) = 0.57, 95% confidence interval (CI): 0.32, 1.01], and the results from the subgroup analysis based on age (>60 years) also revealed that the difference was not statistically significant (RR = 0.49, 95% CI: 0.23, 1.04). Conclusion: Compared with controls, intraoperative subanesthetic dose of ketamine/esketamine has no advantage in preventing POCD in patients, or in elderly patients. This study provides reference data for POCD research and clinical drug intervention strategies. Registration: Prospective Register of Systematic Reviews (PROSPERO; registration number CRD42023401159).